Penerapan Green Accounting: Strategi Keberlanjutan Dan Implikasinya Terhadap Kinerja Keuangan - Ni Luh De Erik Trisnawati; Komang Aryasa (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the implementation of green accounting as a sustainability strategy in the villa industry and its implications for financial performance, as measured by the profitability ratios of Return on Assets (ROA) and Return on Equity (ROE). The research adopts a descriptive quantitative approach, with data collected through interviews, direct observations, and documentation of Villa Sanglung’s financial reports for the period 2021–2024. The green accounting indicators examined include energy efficiency, water management, waste management, environmental costs, and environmental reporting. The findings indicate that the implementation of green accounting contributes to a more systematic identification and management of environmental costs, thereby supporting improvements in operational efficiency and asset utilization. Although the average ROA and ROE remain relatively low, each at 0.96%, this condition is influenced by seasonal factors such as the low season and the suboptimal management of environmental costs. Nevertheless, the integration of green accounting practices demonstrates the potential to enhance profitability and overall financial performance in the long term. Therefore, this study recommends strengthening the implementation of green accounting as a sustainability-oriented strategy to improve competitiveness and ensure business continuity within the villa industry.